ANÁLISE DA UTILIDADE DAS PENAS EM ROUSSEAU E AS ORIGENS FILOSÓFICAS DO DIREITO PENAL DO INIMIGO - Brito, Fernando Vidal (2020)
Modern punitivism and the constant state of vigilance in modern society find theoretical roots in Günther Jakobs theory of the Criminal Law of the Enemy. Thus, the present dissertation will work on the theoretical origins of the Enemy s Criminal Law, espe